To Investigate the Association between the Extent of Lateral Internal Anal Sphincterotomy and Postoperative Fecal Incontinence in Individuals with Chronic Anal Fissure - Nida Ahmed, Rizwan Ahmed Khan, Aqsa Ismail, Syed Humayun Naeem, Haris Ahmed, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The primary objective of this investigation was to evaluate the prevalence of fecal incontinence after surgery in individuals who underwent open lateral internal anal sphincterotomy up to the dentate line compared to those undergoing anal sphincterotomy (open internal) up to the height of the anal fissure. Methodology: This study was randomized and controlled and was carried out in Abbasi Shaheed Hospital, Karachi, at the department of surgery between February 2021 and July 2022. The study enrolled patients who were 15 years or older and presented to the outpatient department with chronic anal fissure, regardless of gender. Patients with concomitant anal disease, those with previous history of anorectal surgery & those with systemic neurological disease leading to fecal incontinence were excluded. Analysis of the collected data was performed using SPSS version 23. For quantitative variables, such as age, standard deviation and mean were calculated. Conversely, the qualitative variables, such as gender, location of anal fissure, Browning and Park's classification of incontinence, and final outcome(i.e. fecal incontinence at 5th postoperative day), were assessed using percentages and frequency. Results: In this study, 198 individuals who are chorincally suffering from anal fissure were identified and divided into two groups, Group A and B, each consisting of 99 patients. Group A underwent an open lateral internal anal sphincterotomy up to the level of the dentate line (referred to as the "dentate line group"), while Group B received an open lateral internal anal sphincterotomy up to the height of the fissure (known as the "height of fissure group").Fecal incontinence was assessed and compared between both groups on 5th postoperative day by using Browning and Park’s classification. The findings of this investigation indicated that open lateral anal sphincterotomy up to the level of the dentate line was associated with an 11.1% incidence of fecal incontinence, while a 3% incidence of fecal incontinence was observed in individuals who underwent anal sphincterotomy (lateral internal) up to the height of the anal fissure. Practical Implication: present study suggests that lateral internal anal sphincterotomy up to the height of anal fissure may be associated with a lower risk of fecal incontinence compared to the dentate line group. Conclusion: The data obtained from this study suggested that open anal sphincterotomy (lateral internal) up to the height of the anal fissure was linked to reduced incidence rates of postoperative fecal incontinence on the fifth day after surgery, as compared to open anal sphincterotomy (lateral internal) up to the level of the dentate line. Therefore, this modification should be used in future regularly in order to reduce this morbidity. Keywords: Fecal incontinence, Chronic Anal Fissure, Sphincterotomy.